Editorial: Human rights at the border - Molland, Sverre (Anti-Trafficking Review, 2013)
It is with great honour that I introduce the second issue of the Anti-Trafficking Review (ATR). The first issue received an overwhelming response and has placed the journal at the forefront of rigorous analysis and debate relating to human trafficking and human rights. It raised the topic of accountability in anti-trafficking. This issue hopes to further strengthen the ATR’s position as a global, reputable journal on human trafficking. Strengthening the quality of research, analysis, and reflexivity in the trafficking sector is much needed, and I echo Anne Gallagher’s observation as guest editor of the first issue that standards in anti-trafficking research tend to be less rigorous than in other fields of study. My aim as a guest editor is to contribute to addressing this shortfall by bringing together a set of diverse and insightful articles focussing on the nexus of borders and human rights. It is also my hope that this issue will work towards narrowing the divide between practitioners and academics in anti-trafficking. This is reflected in the varied range of contributors. The last few years have witnessed a significant increase in publishing relating to human trafficking worldwide. However, there is limited measured debate and appraisal of this literature within the anti-trafficking sector. For this reason we have decided to include a book review as a way of highlighting recent major publications. The question of borders, migration control, trafficking and human rights raise contested and controversial questions. The editorial team has attempted to include different perspectives, reflected in the debate section in particular. Needless to say, all papers have been subject to double blind peer review.